Using the particle swarm optimization method for the constitutive modeling of AZ31B: Verwendung der Partikelschwarmoptimierungsmethode zur konstitutiven Modellierung der Legierung AZ31B. Issue 10 (19th October 2017) - Li, Z.; Dai, G.; Shi, J.; Jarrar, F.; Ozturk, F.; Sheikh‐Ahmad, J.
Abstract: The magnesium alloy AZ31B has a great potential for lightweight applications that do not require high strength. The superplastic forming method is already being used to form this alloy into complex lightweight components. However, in order to provide accurate predictions of the superplastic process of AZ31B, suitable constitutive models should be established. In this paper, the particle swarm optimization method is used to identify the parameters of a suitable constitutive model. High temperature bulge experiments are used to validate the model. Results indicate that the proposed power law model gives more accurate predictions for the lower strain rates.